Breaking the gridlock: Regulation of dietary supplements in the United States. Issue 3 (2nd November 2015) - Kapoor, Akshay; Sharfstein, Joshua M.
Abstract : Despite increasing use of dietary supplements by millions of consumers, regulation of these products has not kept pace with changes and risks in the market. A major reason for this policy gridlock is the inability of different parties to come to an agreement on a path forward. The purpose of this paper is to set out a new framework for regulation in which consumers, industry, and regulators can all find common ground. This framework is based on a conceptual shift from 'benefit versus risk', the model for prescription drugs, to 'access with safety'. Steps should include registration of all dietary supplements to permit easier enforcement against rogue products, a stronger disclaimer explaining the limited role of FDA in evaluating structure/function product claims, the establishment of standard laboratory techniques for characterization of products, and more clear authority for the agency when safety concerns arise. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Despite use of dietary supplements by millions of consumers, regulation of these products has not kept pace with changes and risks in the market. This paper sets out a new framework for regulation in which consumers, industry, and regulators can all find common ground. This framework is based on a conceptual shift from "benefit versus risk, " the model for prescription drugs, to "access with safety."